Edukasi Pencegahan Peningkatan Darah pada Pasien Hipertensi Menggunakan Tanaman Obat di Wilayah Dusun 3 Batu Menyan Baru Desa Sukajaya Lempasing Kabupaten Pesawaran - Eka Trismiyana; Marlina Agustina; Andi Bunga Silvia; Dian Angen Saputra; Adinda Wulan Adha; Refsi Erpiyana; Raihan Saputra; Imanda Satria; Partur Khorip; Yuniati Yuniati; Budiarti Budiarti (Pusat Riset dan Inovasi Nasional, 2024)
Hypertension is a disease that causes high morbidity. Based on the results of the 2018 Basic Health Survey (Riskusdas), the prevalence of hypertension in the Indonesian population aged 18 years and over reached 34.1%. This number has increased compared to the 2013 Riskesdas report. Treatment with antihypertensive drugs is traditionally associated with high costs, and the side effects of these drugs can also cause other diseases if they are not appropriate and treatment is not adhered to. Currently, there are types of medicinal plants that are used to treat various diseases. The aim of this activity is to increase respondents' knowledge regarding preventing increased blood pressure in hypertension sufferers by using medicinal plants. It was found that respondents were very enthusiastic about listening to the material presented by the presenters. Medicinal plants are an alternative way to control blood pressure. Many medicinal plants are effective in lowering blood pressure, one of which is bay leaves.